De Vlaamse wooncode, lokaal woonbeleid en woonkwaliteit : bronnenboek - De Smedt, Peter; Hubeau, Bernard; Janssens, Erwin (Brugge: Die Keure, 1999)
"Redactie : Peter De Smedt, Bernard Hubeau, Erwin Janssens"